Modified carbon black/nylon 6 fibres with excellent antistatic and mechanical properties. (18th December 2019) - Xin, Zhang; Shanshan, Yin; Yang, Meng; Jian, Han; Juanjuan, Su
Abstract : Nylon 6 (PA6) fibre has many advantages such as high strength, wear resistance, light weight, and good elasticity. However, PA6 fibre is prone to deformation in use and the antistatic ability is poor. In this Letter, the dispersion of carbon black (CB) was improved by physical methods and then added to the nylon 6 (PA6). The authors had studied that the dispersion of modified and unmodified CB in PA6 fibres with excellent mechanical properties and electrical conductivity. The results of Zeta potential and particle size test showed that the size of the CB particle modified was decreased and the absolute value of Zeta potential on the surface was increased. The results of scanning electron microscopy showed that the CB had a good dispersion in PA6; the results of thermogravimetric and Fourier transform infrared analysis showed that polystyrene sodium sulphonate was successfully coated on the surface of CB; when 5% modified CB was added in PA6 fibres, the mechanical properties of PA6 were hold up well. Interestingly, when 5% CB modified was added in PA6 fibres, the resistance of CB modified/PA6 fibre with excellent mechanical properties was reached up to 4.89 × 10 11 Ω.